Manajemen Risiko Pekerjaan Welding Block pada Proyek Barge Mounted Power Plant - Sahilah Amrina Rosadah; Syifaul Lailiyah; Denny Ardyanto; David Nur Taufiq (Yayasan Literasi Sains Indonesia, 2024)
Occupational diseases and occupational accidents occur frequently in Indonesia, but are still not well recorded. Welding is a process carried out to form joint parts of the ship's hull. Types of dangers that occur as a result of welding include exposure to ultraviolet and infrared radiation, inhalation of fume in welding, fire, electric shock. The aim of this research is to identify occupational health and safety risks in block welding work on the Barge Mounted Power Plant (BMPP) project. The research method used in this research is descriptive qualitative analysis using the Job Hazard Analysis method. The results of the research show that every work step process carried out by welding workers has the potential for danger which can cause work accidents or work-related diseases. There are five welding activity processes which can cause danger, with the most common being the welding process activities in the inside joint block of BMPP. In conclusion, prevention and control are identified based on each activity in the entire process, especially in the work process. In the work process, prevention and control of hazardous risks is carried out using a hierarchy of control analysis.